(untitled) (Tanzania Medical Journal, 2015)
The cytoskeleton is a system of structural protein primarily involved in the cellular architectural maintenance, intracellular transport, cell division and movement. The classical major components of the cytoskeleton are microtubules, intermediate filaments and microfilaments. Traditionally the microtubules are involved in intracellular transport and organelle structural support. Intermediate filaments provide a rigid structural support to the cell while the microfilaments maintain the cellular surface architectureand support movement and contraction. Emerging evidences however are challenging this classical view of cytoskeleton functions which calls for further investigation. The present study investigates the structural role of the three classical cytoskeletal elements in the maintenance of cell shape and architecture. The study exploits the high resolving power of the confocal microscopy in displaying subcellular components of intact cells, coupled with differential interference imaging. The use of monoclonal antibodies in immunocytochemical staining increases the detection efficiency of the structural details of the cytoskeleton. The present study has empirically demonstrated that actin filaments provide a crucialmechanical support and maintain its contents in space. Intermediate filaments, while they contribute to the cell architectural support theytypically sustain the nucleus and associated structures in spatial proximity inside the cell. Microtubule filaments exhibit no apparent involvement in cellular architecture maintenance. This study has highlighted the specificstructural functions of the classical cytoskeletal elements in which actin filaments play the most important role. These results are important in such areas as cancer research and in pathogen entry and internalization into the cell.